Naturally Occurring Wound Healing Agents: An Evidence-Based Review - G. Karapanagioti, E.; N. Assimopoulou, A. (Current Medicinal Chemistry, 2016)
Nature constitutes a pool of medicines for thousands of years. Nowadays, trust in nature is increasingly growing, as many effective medicines are naturally derived. Over the last decades, the potential of plants as wound healing agents is being investigated. Wounds and ulcers affect the patients’ life quality and often lead to amputations. Approximately 43,000,000 patients suffer from diabetic foot ulcers worldwide. Annually, 25 billion are expended for the treatment of chronic wounds, with the number growing due to aging population and increased incidents of diabetes and obesity. Therefore a timely, orderly and effective wound management and treatment is crucial. This paper aims to systematically review natural products, mainly plants, with scientifically well documented wound healing activity, focusing on articles based on animal and clinical studies performed worldwide and approved medicinal products. Moreover, a brief description of the wound healing mechanism is presented, to provide a better understanding. Although a plethora of natural products are in vitro and in vivo evaluated for wound healing activity, only a few go through clinical trials and even fewer launch the market as approved medicines. Most of them rely on traditional medicine, indicating that ethnopharmacology is a successful strategy for drug development. Since only 6% of plants have been systematically investigated pharmacologically, more intensified efforts and emerging advancements are needed to exploit the potentials of nature for the development of novel medicines. This paper aims to provide a reliable database and matrix for thorough further investigation towards the discovery of wound healing agents.
Keywords: Cicatrization